1985
DOI: 10.1111/j.1559-1816.1985.tb00903.x
|View full text |Cite
|
Sign up to set email alerts
|

The Aye of the Beholder: Susceptibility to Sexism and Beautyism in the Evaluation of Managerial Applicants1

Abstract: Sex‐typed college students (16 males and 16 females) and androgynous college students (16 males and 16 females) evaluated the resumes of fictitious applicants for a managerial position described as requiring interpersonal competencies. The applicant's physical attractiveness, qualifications, and sex were systematically varied in the resumes. Five‐way analyses of variance were performed on the hiring decisions about the applicants and the perceived attractiveness, masculinity, femininity, and social desirabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
2
2

Year Published

1993
1993
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(75 citation statements)
references
References 32 publications
3
65
2
2
Order By: Relevance
“…Furthermore, research has consistently shown that friendly nonverbal behaviors, especially eye contact, smiling, hand gesturing, and head nodding, are associated with higher interview evaluations (e.g., Anderson, 1991;Anderson & Shackleton, 1990;Burnett & Motowidlo, 1998;Cash & Kilcullen, 1985;DeGroot & Motowidlo, 1999;Forbes & Jackson, 1980;Gifford, Ng, & Wilkinson, 1985;Hollandsworth, Kazelskis, Stevens, & Dressel, 1979;Imada & Hakel, 1977;McGovern, Jones, Warwick, & Jackson, 1981;Motowidlo & Burnett, 1995;Parsons & Liden, 1984;Rasmussen, 1984). This leads to the following hypothesis, which basically attempts to replicate prior findings of a relationship between IM use (both verbal and nonverbal) and interview ratings.…”
Section: The Relationship Between Im Use and Im Effectivenesssupporting
confidence: 65%
“…Furthermore, research has consistently shown that friendly nonverbal behaviors, especially eye contact, smiling, hand gesturing, and head nodding, are associated with higher interview evaluations (e.g., Anderson, 1991;Anderson & Shackleton, 1990;Burnett & Motowidlo, 1998;Cash & Kilcullen, 1985;DeGroot & Motowidlo, 1999;Forbes & Jackson, 1980;Gifford, Ng, & Wilkinson, 1985;Hollandsworth, Kazelskis, Stevens, & Dressel, 1979;Imada & Hakel, 1977;McGovern, Jones, Warwick, & Jackson, 1981;Motowidlo & Burnett, 1995;Parsons & Liden, 1984;Rasmussen, 1984). This leads to the following hypothesis, which basically attempts to replicate prior findings of a relationship between IM use (both verbal and nonverbal) and interview ratings.…”
Section: The Relationship Between Im Use and Im Effectivenesssupporting
confidence: 65%
“…Attractiveness has been found to affect an employer's judgment about a job applicant (Beehr & Gilmore, 1982;Benson, Severs, Tagenhorst, & Loddengaard, 1980;Cann, Siegfiied, & Pearce, 1981;Cash, Gillen, & Bums, 1977;Cash & Kilcullen, 1985;Dipboye, Arvey, & Terpstra, 1977;Dipboye, Fromkin, & Wiback, 1975;Gilmore, Beehr, & Love, 1986;Heilman & Saruwatari, 1979;Shahani, Dipboye, & Gehrlein, 1993). Research has also shown that when jobs have been stereotyped as either being appropriate for males or for females, job applicants opposite those stereotypes are viewed less favorably for the job (Cash et al, 1977;Heilman & Saniwatari, 1979).…”
Section: Attractiveness and Expected Achievementmentioning
confidence: 99%
“…Attractive people enjoy many advantages in life [12,13]: they are judged as happier, smarter, more successful, socially adept and warm [14]. At work, they command better jobs with higher salaries and faster promotions [15]. In social communication, women with even skin coloration receive more visual attention [16], enabling better interpersonal relationships.…”
Section: Introductionmentioning
confidence: 99%